Interventions to reduce stress and prevent burnout in healthcare professionals supported by digital applications: a scoping review - Adam, Daniela; Berschick, Julia; Schiele, Julia K.; Bogdanski, Martin; Schröter, Marleen; Steinmetz, Melanie; Koch, Anna K.; Sehouli, Jalid; Reschke, Sylvia; Stritter, Wiebke; Kessler, Christian S.; Seifert, Georg (Frontiers in Public Health, 2023)
Aim Healthcare professionals are at increased risk of burnout, primarily due to workplace-related stressors. The COVID-19 pandemic has further increased this risk. Different interventions exist with varying degrees of effectiveness; little is reported on the content and implementation of such programs. This review fills this gap, with attention to recent programs using digital components. Methods PubMed, Embase, PsycInfo, and Google Scholar were searched between January 24th and 28th, 2022, limited to the last 5 years (≥2017). Articles were included if they (1) focused on stress reduction or burnout prevention for nurses and medical doctors within workplace health promotion for nurses or medical doctors, (2) included a digital program component, (3) were conducted in high-income country contexts, and (4) were clinical studies published in English or German. Data was extracted using a priori designed spreadsheets. A group of at least 2 authors at each stage carried out the screening, selection, and data extraction. Results The search strategy identified 153 articles, all except 7 were excluded. Two studies were conducted in the USA, two in Spain, one in the Netherlands, Poland, and Korea each. Four studies used a randomized study design, all but one had a control group. A wide range of outcome measures was used. The types of interventions included an adapted mindfulness-based stress reduction program combined with aspects of behavioral therapies, cognitive behavioral therapy, or acceptance and commitment therapy. The digital components used were apps (4 studies), a digital platform, blended learning, and a web-based intervention (1 study each). Six studies focused on individual interventions, one included organizational interventions. Conclusion Despite an acute burnout crisis in the healthcare sector, only seven recent interventions were found that integrated digital components. Several problems emerged during the implementation of the interventions that made it clear that organizational support is urgently needed for successful implementation. Although interventions for stress reduction and burnout prevention should combine individual and organizational measures to be as successful as possible, this was only partially the case in one of the intervention programs. The results of this scoping review can be used to further develop or optimize stress and burnout prevention programs.